Design of Single-Bit Fault-Tolerant Reversible Circuits - Gaur H.M.; Singh A.K.; Mohan A.; Fujita M.; Pradhan D.K. (My University, 2025)
This article introduces redundant design approaches for reversible circuits (RCs) that have the ability to detect and tolerate single-bit fault without the need of conventional voting scheme. Experiments preformed show that the proposed scheme reduces the gate cost on average with up to 28% as compared with tri-modular redundant circuits. RCs have direct relation with quantum computation which are largely to loss of energy levels due to the phenomenon of quantum decoherence that cause single point failures.